Abdominal obesity-related risk factors in children from public schools of Barbacena, Minas Gerais, Brazil - Mariana das Dores Paiva Canuto; Adriele Vidal Lucas Silva; João Victor Martins; Marlene de Melo Fonseca; Nathália Sernizon Guimarães; Anne Danieli Nascimento Soares; Júnia Maria Geraldo Gomes
ABSTRACT Objective: To evaluate the sociodemographic and lifestyle factors associated with abdominal obesity in children from public schools in Barbacena, state of Minas Gerais, Brazil. Methods: This is a cross-sectional study conducted on 326 students aged 7 to 9 years from public schools in the urban area of the city. Anthropometric data included body weight, height, body mass index according to age, waist circumference, and waist-to-height ratio. Food consumption was evaluated using the Previous Day Food Questionnaire. Abdominal obesity was assessed based on waist circumference and waist-to-height ratio. The bivariate and multivariate analyses were performed by logistic regression, estimating the crude and adjusted odds ratio (OR), with 95% confidence interval. Results: The prevalence of overweight was 30.7%; whereas the prevalence of abdominal obesity was 9.2 and 12.6% according to waist circumference and waist-to-height ratio, respectively. Boys (OR 2.76; 95%CI 1.22-6.25) and children from central schools (OR 2.73; 95%CI 1.08-6.80) presented an increased chance of abdominal obesity according to waist circumference. Abdominal obesity according to waist-to-height ratio was associated with the central location of the schools (OR 2.18; 95%CI 1.02-4.63) and the habit of skipping supper (OR 2.01; 95%CI 1.00-4.09). Conclusions: The findings showed that being a boy, studying in a central school, and skipping supper were the main risk factors associated with abdominal obesity.